Communication to Find Water Intake Location within Public Private Partnership between Tangerang Government Authority and PT Aetra Air Tangerang - Binsar Naipospos; Aulia Paramita (Journal of Regional and City Planning, 2019)
This article aimed to explore an effective communicative planning approach in infrastructure development using the PPP scheme, incorporating the complementary concepts of communicative planning and critical pragmatism. From 2005 to 2007, an epidemic disease severely threatened the District of Tangerang, which was found to be caused by poor water quality and improper clean water management. The limited local government budget and capability was a double issue that encouraged the participation of the private sector in building a drinking water infrastructure by using a public private partnership (PPP) scheme. One of the scopes of the project was finding the best tapping intake location for the Drinking Water Supply System (SPAM "“ Sistem Penyediaan Air Minum). Rather than being simply an infrastructure project, PPP is a complex field of power relations among actors and groups, since it is implemented across institutions and jurisdictions. It took three years of intensive communication between governments, private parties, and lawmakers from the district, the provincial, and the national level. Both primary and secondary data were analyzed with a qualitative approach to gain a deeper understanding of the case study. The result showed that to make the PPP scheme successful, the planners involved in the PPP team dealt with power imbalances by creating networks with the other actors and making them engaged in bargaining processes to reach the desired agreements. Abstrak. Artikel ini bertujuan untuk mengeksplorasi pendekatan perencanaan komunikatif yang efektif dalam pengembangan infrastruktur dengan menggunakan skema Kerjasama Pemerintah Badan Usaha (KPBU) melalui penelitian perencanaan komunikasi praktis di Indonesia. Dari tahun 2005 hingga 2007 suatu penyakit epidemik diare menyerang parah Kabupaten Tangerang yang disebabkan oleh buruknya kualitas air dan pengelolaan air bersih yang tidak tepat. Terbatasnya anggaran pemerintah daerah dan ketidak-mampuan anggaran adalah dua masalah besar yang mendorong perlunya partisipasi sektor swasta untuk membangun infrastruktur air bersih melalui skema KPBU. Salah satu masalah pelik yang menjadi fokus ruang lingkup penelitian ini adalah bagaimana menentukan lokasi pengambilan sadapan air untuk Sistem Penyediaan Air Minum (SPAM). Menentukan lokasi tempat penyadapan air dalam proyek KPBU adalah suatu hal yang rumit karena berhubungan dengan kekuasaan antar berbagai aktor dan kelompok. Diperlukan sekitar tiga tahun untuk berkomunikasi secara intensif antara pemerintah, swasta, legislatif baik di tingkat kabupaten, provinsi, dan pusat. Data primer dan sekunder telah dianalisis dengan metoda pendekatan kualitatif untuk menelusuri dan memberikan pemahaman yang lebih mendalam untuk kasus studi. Hasilnya menunjukkan bahwa untuk menyukseskan kesepakatan dimana tempat lokasi penyadapan air disepakati dalam skema KPBU, para perencana yang ada dalam tim KPBU harus mengatasi adanya ketidakseimbangan kekuatan dan kekuasaan antar berbagai aktor.  Semua aktor harus berkomunikasi dengan saling bertukar-menukar ide, data dan informasi agar kesepakatan dapat tercapai sesuai keinginan.Kata kunci. PPP, perencanaan komunikatif, infrastruktur air bersih.